Democratic Republic of Sao Tome and Principe : Request for a Three-Year Arrangement Under the Extended Credit Facility and Cancellation of the Current Arrangement Under the Extended Credit Facility. (IMF Staff Country Reports; Country Report ;, 2015)
EXECUTIVE SUMMARY Context: Sao Tome and Principe's economic development is constrained by its insularity, fragility, limited resources, and low capacity as a small island state. The current ECF arrangement is set to expire on July 19, 2015, with four reviews outstanding. Program performance was satisfactory during the first year and half of implementation but went off track in early 2014 upon the contracting of a loan resulting in nonobservance of the performance criterion on non-concessional debt, and expenditure slippages in the run up to national elections further delayed program resumption. In the meantime, the key assumptions of the macroeconomic framework agreed under the current program changed significantly due to a lower probability of commercial oil production. Extended Credit Facility. The Sao Tomean authorities have requested a three-year arrangement under the ECF in an amount equivalent to SDR 4,440,000 (60 percent of quota) to rebuild buffers and catalyze financing in support of their medium-term economic reform program. The existing program would be cancelled. Main elements of the program. The program seeks to address the high debt vulnerability while also creating the conditions for sustained growth, anchored by the PRSP II. This involves reforms to: -- Strengthen domestic revenue mobilization, expenditure rationalization, public debt management, and public financial management to restore fiscal discipline and reduce the risk of debt distress. -- Introduce a comprehensive plan to eliminate the stock of arrears and also prevent the accumulation of new arrears. -- Enhance the capacity of key government institutions through well-tailored technical assistance (TA). -- Enhance financial sector stability through strengthened supervisory, regulatory, crisis management and bank resolution frameworks.